The Role of Innate Immune Cells in Nonalcoholic Steatohepatitis - Cai, Jingjing; Zhang, Xiao‐Jing; Li, Hongliang (Hepatology (Baltimore, Md.), 2019)
Inflammation and metabolic dysfunction are hallmarks of nonalcoholic steatohepatitis (NASH), which is one of the fastest‐growing liver diseases worldwide. Emerging evidence indicates that innate immune mechanisms are pivotal drivers of inflammation and other pathological manifestations observed in NASH, such as hepatosteatosis, insulin resistance (IR), and fibrosis. This robust innate immune reaction is intrinsic to the liver, which is an important immunological organ that contains a coordinated network of innate immune cells, including Kupffer cells (KCs), dendritic cells (DCs), and lymphocytes. Hepatocytes and liver sinusoidal endothelial cells (LSECs) are not formally innate immune cells, but they take on immune cell function when stressed. These cells can sense excess metabolites and bacterial products and translate those signals into immune responses and pathological hepatic changes during the development of NASH. In this review, we take a historical perspective in describing decades of research that aimed to identify the key molecular and cellular players in the innate immune system in the setting of NASH. Furthermore, we summarize the innate immune cells that are involved in the progression of NASH and illustrate how they sense disturbances in circulating metabolic factors by innate immune receptors and subsequently initiate the intercellular signaling cascades that lead to persistent inflammation and progression of hepatic complications.